Functional dietary lipids : food formulation, consumer issues and innovation for health - Sanders, Thomas (Woodhead Publishing in food science, technology, and nutrition., 2024)
Functional Dietary Lipids: Food Formulation, Consumer Issues and Innovation for Health, Second Edition discusses this important component of the human diet and the ways it plays an essential functional role. As with the previous edition, this book covers the functionality and nutritional benefits of dietary fat in food in terms of formulation, manufacturing and innovation for health. It contains approximately 35% new content, including 5 new chapters as well as updated content in previous chapters. New content covers the health effects of fat-soluble compounds, the sustainability aspects of vegetable oil production; process engineering of fats to improve functionality and quality, and more. This second edition also includes updated data on regulations, including nutritional profiling, signposting, taxation and advertising restrictions, and the regulatory approval of novel sources of lipids. This book will be a useful reference for those wanting to explore human nutrition and dietary lipids as well as those involved in decision-making surrounding food formulation and manufacturing.